Efektivitas Ukuran Blok Campuran Tanah dan Hydraulic Loading Rate Pada Multi Soil Layering Guna Menurunkan Parameter Fosfat dan Surfaktan Anionik di Usaha Binatu - Tarikh Azis Ramadani; Novi Eka Mayangsari; Mitha Amelia Anjani (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
The laundry business is one of the business that produces phosphate and anionic surfactant parameters that cause eutrophication and environmental pollution. Parameters of phosphate and anionic surfactants can be reduced using multi soil layering with two stages. This study aims to analyze the effect of soil mixed block size and hydraulic loading rate on reducing pollutant concentration. The materials used in this study are andosol soil, rice husk charcoal and iron powder. The permeable layer uses gravel and pearlite media. The reactor is made of acrylic with a length of 50 cm, a width of 15 cm and a height of 50 cm. Multi soil layering systems successfully reduce concentrations to 98,603% for phosphate parameters and 99.99% for anionic surfactant parameters. The decrease in phosphate parameters and anionic surfactants is caused by physical and chemical adsorption processes by soil components and rice husk charcoal. The decrease in the parameters of anionic surfactants is also helped by the process of biodegradation of microbes in the soil.